Magnetic Gels in Skin Cancer Treatment: A Review of Potential Applications in Diagnostics, Drug Delivery and Hyperthermia - Marcos Luciano Bruschi; Glécilla Colombelli de Souza Nunes (MDPI AG, 2023)
Skin cancer (SC) is affecting an increasing number of people worldwide. Its lesions affect mainly the most exposed regions of the skin. SC is classified into to main categories: non-melanoma (basal cell carcinoma of the epidermis and squamous cell carcinoma) and melanoma (the abnormal proliferation of melanocytes, which is rarer, more hazardous, and more deadly). Prevention and early diagnosis are important actions, and surgery is often considered. After the removal of cancerous lesions, the local administration of medicine can guarantee anticancer therapeutic action, rapid healing and the recovery of tissue, ensuring the absence of recurrence. Magnetic gels (MGs) have attracted increased attention regarding their pharmaceutical and biomedical applications. They are magnetic nanoparticles (e.g., iron oxide nanoparticles) dispersed in a polymeric matrix, which constitute adaptive systems under a magnetic field. MGs can combine magnetic susceptibility, high elasticity, and softness, and are thus useful platforms for diagnostics, drug delivery, and also for hyperthermia. This manuscript reviews MGs as a technological strategy for the treatment of SC. An overview of SC and the treatment, types, and methods of preparing MGs are discussed. Moreover, the applications of MGs in SC and their future perspectives are considered. The combination of polymeric gels and magnetic nanoparticles continues to be investigated, and new products must hit the market. Clinical trials and new products are expected, due to the important advantages of MGs.